Encoding Motion Events in Mandarin and Italian: Theoretical Issues, Teaching Materials, and Implications for CFL/CSL Teaching - Carmen Lepadat (Quaderni di Linguistica e Studi Orientali)
he encoding of motion events shows significant cross-linguistic variation: Mandarin, a satellite-framed language, encodes path information in secondary elements, whereas Italian, a verb-framed language, lexicalizes path directly within verbal roots. This typological difference, rooted in Talmy (2000)’s framework, poses challenges for Italian-speaking learners in acquiring Mandarin’s primary device for motion encoding, directional verbal complexes (DVCs). These constructions are sequences of verbal morphemes that encode multiple motion components simultaneously, including manner of motion, path, and perspective. In contrast, Italian strategies for motion encoding tend to emphasize trajectory or path over the manner of motion. Through an analysis of CFL (Chinese as a Foreign Language) textbooks and grammars used in three main Italian universities, this study identifies critical gaps, including insufficient explanations of the syntactic and–more notably–semantic constraints impacting DVC word order, object positioning, and aspectual marking. Findings indicate that a comparative, typologically aware approach – leveraging Italian constructions with similar functions such as syntagmatic verbs – could bridge these gaps, fostering a more accurate understanding of DVCs. The study recommends enhancing teaching materials to better represent the full syntactic and semantic range of DVCs, aiding learners in mastering the complexities of Chinese motion event encoding.